2020
DOI: 10.1038/s41598-019-56743-x
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor FXR inhibits Glucagon-Like Peptide-1 secretion in response to microbiota-derived Short-Chain Fatty Acids

Abstract: the gut microbiota participates in the control of energy homeostasis partly through fermentation of dietary fibers hence producing short-chain fatty acids (SCFAs), which in turn promote the secretion of the incretin Glucagon-Like Peptide-1 (GLP-1) by binding to the SCFA receptors FFAR2 and FFAR3 on enteroendocrine L-cells. We have previously shown that activation of the nuclear farnesoid X Receptor (FXR) decreases the L-cell response to glucose. Here, we investigated whether FXR also regulates the SCFA-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 50 publications
1
41
0
1
Order By: Relevance
“…Intestinal FXR inhibition regulates glucose and lipid homoeostasis partly through the gut–liver axis and gut–adipose axis 20 22 . Recent studies indicated FXR inhibition in L cells stimulates GLP-1 production and glucose-induced GLP-1 secretion 14 , 21 , 23 , 24 . Therefore, de-activation of intestinal FXR may be the potential strategy for metabolic syndrome treatment 14 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal FXR inhibition regulates glucose and lipid homoeostasis partly through the gut–liver axis and gut–adipose axis 20 22 . Recent studies indicated FXR inhibition in L cells stimulates GLP-1 production and glucose-induced GLP-1 secretion 14 , 21 , 23 , 24 . Therefore, de-activation of intestinal FXR may be the potential strategy for metabolic syndrome treatment 14 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These observations have been replicated in studies with different L-cell lines (i.e., NCI-H736 [ 28 ] and STC-1 [ 29 ]). In a similar manner, GW4064 blunted the GLP-1 response to short-chain fatty acids (SCFA) in both GLUTag and NCI-H716 cell lines [ 30 ]. Consistent with these observations, FXR-deficient mice exhibited increased GLP-1 secretion in response to both dietary fiber, which increases colonic SCFA [ 30 ], and oral glucose [ 31 ].…”
Section: Effects Of Bile Acids On Gastrointestinal Hormone Secretionmentioning
confidence: 99%
“…In a similar manner, GW4064 blunted the GLP-1 response to short-chain fatty acids (SCFA) in both GLUTag and NCI-H716 cell lines [ 30 ]. Consistent with these observations, FXR-deficient mice exhibited increased GLP-1 secretion in response to both dietary fiber, which increases colonic SCFA [ 30 ], and oral glucose [ 31 ]. Oral intake of GW4064 (10 mg/kg, 2 doses over 12 h) also decreased active GLP-1 levels in the plasma of mini-pigs [ 28 ].…”
Section: Effects Of Bile Acids On Gastrointestinal Hormone Secretionmentioning
confidence: 99%
“…In contrast, FXR agonism was shown to downregulate GPR43 expression and attenuate SCFAinduced GLP-1 response both in ex vivo colonoids and in vivo, an effect that could be reversed by FXR deficiency. 89 Thus, FXR is an important factor that, through regulation of expression or activation of other receptors and through cross-talk with the gut microbiota, serves to regulate GLP-1 levels. However, the effects mediated by FXR are complex, as it can up-or downregulate expression of hormones, depending on interaction with other receptors.…”
Section: Bile Acids-fxrmentioning
confidence: 99%